Some Considerations about “Poetic Language”: “Lyrical Poetry” as Literary Gender - Aguirre Gómez, Carlos Enrique (2024)
Based on well-known theorists of literature, the author of this essay makes a review of the following concepts: literature, literary text, poetic sign, and linguistic structure in order to understand what poetry is as a literary expression.